Penerapan Model Waterfall Pada Sistem Informasi Penjualan Berbasis Web - Sidik Sidik; Arief Maulana; Bilal Abdul Wahid (Universitas Mercu Buana, 2020)
Technology has become a necessity that cannot be separated from lifestyle, even in its development humans are increasingly dependent on technology. In the field of business, the development of information technology has had a significant impact in increasing business activities, especially in terms of data management that provides support for business decision making and in terms of improving services. Everest Chicken Penyet Restaurant is a company engaged in the sale of food in the form of fried chicken, penyet chicken, sweet grilled chicken, spicy grilled chicken, duck penyet, catfish penyet and many others. At present the sales system at Ayam Penyet Everest Restaurant has not used a computerized system, the workmanship is still manually where it still uses a handwriting system to recap the ordered product data and the sales process. The research method used is a research and development method with the waterfall model. The results of this study are customers get information about the latest menus quickly on the Ayam Penyet Everest website, so that it becomes more efficient. With a web-based sales information system this makes the company's performance better and more professional in its activities..